-46-12x=-8x+46

Simple and best practice solution for -46-12x=-8x+46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -46-12x=-8x+46 equation:


Simplifying
-46 + -12x = -8x + 46

Reorder the terms:
-46 + -12x = 46 + -8x

Solving
-46 + -12x = 46 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-46 + -12x + 8x = 46 + -8x + 8x

Combine like terms: -12x + 8x = -4x
-46 + -4x = 46 + -8x + 8x

Combine like terms: -8x + 8x = 0
-46 + -4x = 46 + 0
-46 + -4x = 46

Add '46' to each side of the equation.
-46 + 46 + -4x = 46 + 46

Combine like terms: -46 + 46 = 0
0 + -4x = 46 + 46
-4x = 46 + 46

Combine like terms: 46 + 46 = 92
-4x = 92

Divide each side by '-4'.
x = -23

Simplifying
x = -23

See similar equations:

| 6m+3m=6m-9 | | 1/5p-3=9 | | (5xy)-2= | | 4(x-5)=-36 | | Y=-2x^4-6x^2+8 | | 8*n= | | 1.3x-1.9=1.9 | | 5x^2+2=16x | | X+2*x+10*y=295 | | -4(2v+3)=28 | | g(5)=6x+7 | | .55*5= | | y-7=6/7(x-6) | | 7lnx-3(lnx^3+5lnx)=0 | | 1.2y+3=.36x | | -51-9x=-2x+95 | | x+7=2(x) | | y-3=4(x+5) | | 3x+11+5x-9=360 | | 2-18/x^2 | | 80+11x-10=360 | | 2x+(-5)=3x+(-1) | | y-7=-5(x+8) | | secx-tanx=cscx-1/cotx | | 2m-0.5=1.7 | | 12y-30=18 | | -4(w+7)=24 | | 8=2x/0.200-x | | y+6=-7(x+5) | | (18-8x)/4x | | -11=x-5-1 | | 2y+4x-3w=19 |

Equations solver categories